A decade of action in transport : an evaluation of World Bank assistance to the transport sector, 1995-2005 (World Bank e-Library., 2007)
The World Bank committed 30.6 billion in transport-related projects during the past decade, making it one of the largest sectors. The evaluation looks into the Bank's experience in the sector, and assesses the institution's interventions, the impact of rapid transport sector expansion, and its readiness to meet the challenges ahead.